REALISING THE POTENTIAL OF MANUFACTURING EXECUTION SYSTEMS - Van Dyk, L.; Van Schoor, C.D. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The term Manufacturing Execution System (MES) was created by Advanced Manufacturing Research (AMR) in 1990 to describe a suite of software products, which enables the execution of manufacturing through the integration of the plann ing and control systems of an enterprise. The evolution of Manufacturing Execution Systems is a result of the evolution of manufacturing strategies, manufacturing planning and control systems , as well as the evolution of information technology. In this article this evolution is investigated, current business models are evaluated and an MES Function Matrix is proposed to address inadequacies of these models . AFRIKAANSE OPSOMMING: Die term Vervaardigingsuitvoeringstelsels ("Manufacturing Execution System" - MES) is in 1990 deur Advanced Manufacturing Research (AMR) geskep om die stel sagtewareprodukte te beskryf, wat die uitvoering van vervaardigingsplanne moontlik maak deur die integrasie van die beplanning- en beheerstelsels van 'n ondememing. Die evolusie van MES is die resultaat van die ontwikkeling van vervaardigingstrategiee, vervaardingsbeplanning- en beheerstelsels, asook die ontwikkeling van inligtingstegnologie. In hierdie artikel word die evolusie van MES ondersoek, besigheidsmodelle word geevalueer en 'n MES Funksie Matriks word voorgestel om leemtes ten opsigte van hierdie modelle te identifiseer.